RESILIENSI DITINJAU DARI HARGA DIRI PADA SINGLE MOTHER DI DESA AMPLAS - ignatia lia nainggolan (Universitas HKBP Nommensen, 2020)
ABSTRACTS This study aims to fine out the relationship between self esteem and resilience. The hypothesis of this study states that there is a positive correlation between self esteem and resilience, assuming that the higher the self esteem, the higher resilience will be and conversely the lower the resilience, the lower the life satisfaction will be. The subjects of this study were 95 people of the single mother of amplas village. Data were obtained from a scale to measure self esteem and resilience. The calculation was performed by testing requirements analysis (assumption test), which consists of normality test for distribution and linearity test for relationships. Product Moment correlation with SPSS 17 for windows was used in the data analysis. The results in the data analysis showed that the correlation coefficient was 0.677 with p 0.000 (p< 0.05). It shows that there is a positive correlation between self esteem and resilience. The result indicate that the contribution of the given variable, self esteem to resilience is 45.8 percent, while the remaining 54.2 percent is influenced by the other factors that are not examined in this study. Based on these results, it can be concluded that the hyphotesis is acceptable, and there is a positive correlation between self esteem and life resilience.